Biodegradation of the explosive pentaerythritol tetranitrate (PETN) by bacteria isolated from mining environments - Durán, Yerson (2013)
Pentaerythritol tetranitrate (PETN) is the most energetic and recalcitrant detonating used in mining activity being that it has four nitro groups linked by ester bounds, also is considered a persistent organic pollutant in agreement with the Stockholm Convention. In this work the degradation efficiency of PETN by bacteria isolated from mining environments is evaluated. At first, strains that showed growth during three subcultures with PETN as unique source of nitrogen were selected. Before, we identified Bacillus sp. J8A2 and Enterobacter sp. M1B by the 16S rRNA gene partial sequences analysis. Specific growth rate were 0.057 h-1 for J8A2 and 0.042 h-1 for M1B, and specific rate of PETN degradation were 0.72 and 1.16 mmol of PETN/g of protein.h respectively. Moreover, crude extract of J8A2 strain showed a specific activity (U) of 1.03 mmol of PETN/h and a specific activity per protein (U/g) of 138.6 mmol of PETN/g.h.